Treating ecological deficit with debt: The practical and political concerns with green bonds. Issue 114 (August 2020) - Jones, Ryan; Baker, Tom; Huet, Katherine; Murphy, Laurence; Lewis, Nick
Highlights: Green bonds offer to reorient financial capital in support of sustainability. Use-of-proceeds and environmental assurance distinguish green from regular bonds. Practical concerns: protecting product integrity and enhancing product performance. Political concerns: amplifying inequity and prioritising profits over outcomes. Questions of use-value, greenwashing and market design could be (re)considered. Abstract: Recent years have witnessed calls to 'unlock' private capital and unleash a wave of green finance that can address the global environmental crisis. To this end, ample resources are being invested in the rapidly growing market for green bonds : a debt security that links finance to projects that claim environmental benefits. This has placed green bonds in the vanguard of green finance, with a promise of treating our ecological deficit with debt. Such positioning demands close scrutiny of their obstacles, opportunities, and socio-environmental impacts. This paper contributes to this task with a multi-disciplinary review of green bond media articles, grey literature, and academic research. The paper has three key aims. It seeks to provide an introduction to green bonds for scholars who are not fluent in finance. Secondly, it attempts to provide a platform for further green finance research by delineating the major practical and political concerns with green bonds. Finally, it aims to widen our view of the green bond market by putting applied and critical research agendas into direct conversation. The paper concludes by calling for more explicit analysis of what green bonds can actually do; centring an expanded notion of greenwashing in green bond discourse; and pursuing more comparative, case driven research on green bond market development.